Effect of feeding antenna on the scattering pattern of reflector antenna - Dghali, Mohamed (Видавництво Львівської політехніки, 2012)
It is investigated the influence of feeder on the scattering pattern of single reflector antenna with symmetrical parabolic reflector.
Keywords: Scattering pattern; reflector antenna; feeder effect